2020
DOI: 10.3389/fpsyg.2020.565651
|View full text |Cite
|
Sign up to set email alerts
|

Common Ground Information Affects Reference Resolution: Evidence From Behavioral Data, ERPs, and Eye-Tracking

Abstract: One of the most important social cognitive skills in humans is the ability to “put oneself in someone else’s shoes,” that is, to take another person’s perspective. In socially situated communication, perspective taking enables the listener to arrive at a meaningful interpretation of what is said (sentence meaning) and what is meant (speaker’s meaning) by the speaker. To successfully decode the speaker’s meaning, the listener has to take into account which information he/she and the speaker share in their commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 69 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…From research on perspective taking it seems, though, that the shift in perspective is not the only factor causing the observed pattern. According to the approach by Harris ( 2021 ) the default perspective holder should be the narrator and a shift from this perspective should elicit enhanced processing costs (for costs of shifting see Sabbagh and Taylor, 2000 ; Zhou et al, 2010 ; Meinhardt et al, 2011 ; Shi et al, 2011 ; Richter et al, 2020 ). In Figure 5 , however, we see the tendency that d-pronouns that render the narrator's perspective cause comparatively high processing costs in form of the frontal positivity.…”
Section: The Eeg Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…From research on perspective taking it seems, though, that the shift in perspective is not the only factor causing the observed pattern. According to the approach by Harris ( 2021 ) the default perspective holder should be the narrator and a shift from this perspective should elicit enhanced processing costs (for costs of shifting see Sabbagh and Taylor, 2000 ; Zhou et al, 2010 ; Meinhardt et al, 2011 ; Shi et al, 2011 ; Richter et al, 2020 ). In Figure 5 , however, we see the tendency that d-pronouns that render the narrator's perspective cause comparatively high processing costs in form of the frontal positivity.…”
Section: The Eeg Experimentsmentioning
confidence: 99%
“…In electrophysiology, studies observed positive deflections for shifts of perspective. For instance, Richter et al ( 2020 ) used Keysar et al's ( 2000 ) well-known referential communication game to test the influence of common ground information and privileged information. The authors observed an enhanced frontal late positivity for the condition, in which the perspectives of speaker and addressee differed; this required the integration of common ground information while suppressing privileged information (Richter et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation